Mobility indices and doses from 210Po and 210Pb activity concentrations data in Brazilian spas groundwaters - Bonotto, Daniel Marcos [UNESP]; Oliveira, Ana Maria Marinello Assis de [UNESP] (Elsevier, 2017)
210Po and 210Pb activity concentrations in spas groundwaters occurring at São Paulo (SP) and Minas Gerais (MG) states, Brazil, have been reported in this paper with a dual purpose: to compare different indices for evaluating the radionuclides mobility into waters and to evaluate the drinking water quality from dose calculations. The waters (75 sampling points) are extensively used for drinking in public places, bottling and bathing purposes, among other. The samples were taken from springs and wells drilled at different aquifer systems inserted in Paraná and Southeastern Shield hydrogeological provinces. The WHO guideline reference value for 210Pb and 210Po of 0.1 Bq/L in drinking water was not reached for 210Pb but the 210Po levels were equal or above it in four spas groundwaters from MG State. The maximum WHO guidance dose level of 0.1 mSv/yr was also reached or surpassed in them. The 210Pb “mobility index” taking into account the ratio of the weight of the dissolved 210Pb per unit volume of solution to its weight per unit weight of the rock matrix yielded values in the range of 0.01–5.2 kg/m3. Another “mobility index” (Preference Ratio) expressing the ratio of 210Pb and 238U in the waters divided by the ratio of 210Pb and 238U in the rock matrices provided values between 0.004 and 7994. The 210Pb/238U activity ratios of some spas groundwaters suggested preferential 238U transport relative to 210Pb into the liquid phase, whereas the ratio of the 210Pb to 238U mobility indices indicated the opposite. Such finding showed a better usefulness of the mobility indices for evaluating processes affecting the radionuclides release into the liquid phase during the water/rock interactions.
Keywords: 210Po and 210Pb; Radionuclides mobility; Southeastern Brazil; Spas groundwaters